Enhancing Consumer Engagement through Kansei Engineering: A Novel Approach to Sago Rice Packaging Design - Johan, Vonny Setiaries; Riftyan, Emma; Khairany, Septy (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractThe purpose of this study was to produce a sago rice packaging design that suits consumer preferences using the Kansei Engineering method. This study employed a survey method and quantitative analysis. The Kansei words selected in this study included communicative, transparent, informative, practical, safe, brightly colored, attractive, innovative, size-appropriate, unique, strong, creative, distinctive, patterned, and protective of the product (15 words in total). The design elements and sub-elements identified from 10 samples of analog rice packaging were packaging materials (aluminum foil and plastic), labels (digital printing and stickers), packaging forms (standing pouches, side gusset pouches, and sachets), and colors (many colors (>3 colors), few colors (2-3 colors), and plain). The packaging design desired by consumers, based on conjoint analysis, reflected the Kansei words practical, attractive, innovative, unique, creative, distinctive, and patterned. Consumers preferred packaging made of aluminum foil, labeled with digital printing, in the form of a standing pouch, and featuring many colors (>3 colors).Keywords: Kansei Engineering, Kansei word, packaging design plan, sago rice AbstrakTujuan penelitian ini adalah menghasilkan rancangan desain kemasan beras sagu yang sesuai dengan keinginan konsumen menggunakan metode Kansei Engineering. Penelitian ini menggunakan metode survei dan analisis kuantitatif menggunakan metode Kansei Engineering. Kata Kansei yang terpilih pada penelitian ini adalah komunikatif, transparan, informatif, praktis, aman, berwarna terang, menarik, inovatif, ukuran sesuai kebutuhan, unik, kuat, kreatif, berciri khas, bermotif dan melindungi produk (15 kata). Elemen desain dan sub elemen desain yang dipilih berdasarkan identifikasi 10 sampel kemasan beras analog adalah bahan kemasan terdiri dari aluminium foil dan plastik, label kemasan terdiri dari digital printing dan stiker, bentuk kemasan terdiri dari standing pouch, side gusset pouch, dan sachet, dan warna kemasan terdiri dari banyak warna (>3 warna), sedikit warna(2-3 warna), dan polos. Desain kemasan yang diinginkan konsumen berdasarkan kombinasi yang muncul dari hasil conjoint analysis menggambarkan kata kansei praktis, menarik, inovatif, unik, kreatif, berciri khas, dan bermotif dan kemasan dengan bahan aluminium foil, berlabel digital printing, berbentuk standing pouch, dan terdiri banyak warna (>3 warna).Kata kunci: Beras sagu, Kansei Engineering, kata Kansei, rancangan desain kemasan